Kedudukan Peradilan Tata Usaha Negara (PTUN) Sebagai Lembaga Peradilan Khusus di Indonesia dengan Konsekuensinya - Sugita, I Made (VYAVAHARA DUTA, 2024)
Abstract The State Administrative Court as one of the actors of judicial power is an independent judicial environment, separate from the general court, Military Court, and Religious Court, in accordance with the provisions of Article 10 paragraph (1) and paragraph (2) of Law Number 4 of 2004 about judicial power. On this basis, state administrative courts have specificities compared to other courts and have their own consequences. The aim of this research is to determine the position of the State Administrative Court as a special judicial institution in Indonesia and its consequences. This type of research is normative legal research because this research examines statutory regulations, theories or doctrines, conceptual thinking, and previous research related to the object of study in this research. The results of this research show that the consequence resulting from this specificity is that only those that are judged by the State Administrative Court are those related to State Administrative disputes. Article 1 number (10) of Law Number 51 of 2009 states that state Administrative Disputes are disputes that arise in the field of State Administration between individuals or civil legal entities and State Administrative bodies or officials, both at the central and regional levels, as as a result of the issuance of a State Administrative Decree, including employment disputes based on applicable laws and regulations. Keywords: Position, State Administrative Court, and Special